The Turbulent Structure of a Ground Vortex - Barata, Jorge M M (2012)
Laser-Doppler measurements of the velocity characteristics of a ground vortex flow resulting from the collision of a wall jet with a boundary layer are presented and discussed together with flow visualization. In the present study a velocity ratio between the boundary layer and the wall jet of 0.5 was used, and the results confirmed the existence of a very complex vortex flow region in the collision zone near the ground wall. Vorticity values were calculated from the experimental data and revealed negative (clockwise) vorticity near the stagnation point which is an indication of the presence of a small secondary vortex, also detected from the visualization studies but not sufficiently identified from the LDA measurements. The analysis of turbulent energy equation terms using the measured data revealed that production by normal and shear stresses are both very important to the turbulent structure of the impact zone of the ground vortex.